Pengembangan Prototype Sistem Informasi Simpan Pinjam Koperasi Pribadi Manjung Ngawen Klaten - Maria Atik Sunarti Ekowati; Endang Satyawati; Retno Palupi; SM Santi Winarsih (Universitas Boyolali, 2021)
The term cooperative comes from the foreign language co-operation. Cooperative means joint effort. A cooperative is a business unit that collects and distributes funds for members of the cooperative itself. One of the cooperative business units is a savings and loan cooperative. Each member of the Savings and Loans Cooperative must make savings in accordance with the cooperative's provisions. Members can make loans, managed transactions are member savings transactions and member loan transactions. Savings and loan cooperative funds come from cooperative members. Because this savings and loan really helps the needs of members, if this savings and loan facility is dissolved because there is no coordination in data processing on savings and loans, the people in ngawen, manjung, will be less viable for their livelihoods, so that many children drop out of school, the result will be to destroy the nation's development and the state, because of that, it is necessary to develop a Manjung Ngawen Cooperative UMKM Savings and Loan Information System. Development objectives help, facilitate and accelerate cooperative administration in managing transactions. The method used by WatterFall, the result of system development is that the system can help calculate loan interest, loan installments, remaining unpaid loans, share SHU for each member and display data on reports on deposits, loans, and member payments.